Studi Produktivitas Coal Crusher Plant dalam Upaya Pencapaian Target Barging Pada PT. Bukit Biduri Energi Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Irfan Sauri; Harjuni Hasan; Henny Magdalena; Windhu Nugroho; Agus Winarno (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
Bukit Baiduri Energi is a coal mining company operating in Bukit Raya Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. The coal produced has different sizes so it cannot be sold directly. Therefore, it is necessary to carry out a grain size reduction process (crushing) to meet market needs (buyers). The production target of the crushing unit is 128,000 tons/month, based on actual observations in the field, it only produces 110,065.27 tons/month, which means the crusher plant unit only produces 86%, still lacking 14%. Productivity at CP-01 is 317.73 tons/hour and CP-02 is 214.47 tons/hour. The production target has not been achieved due to several constraints (technical and non-technical), it is necessary to conduct a constraint time analysis using a Pareto diagram to determine the efforts that must be made to achieve the production target. For the work efficiency value at CP-01 it is only 27.04% and for CP-02 it is only 31.21 and for the value of the availability of working time of the crusher plant unit, the value at CP-01 is MA = 81.94%, PA = 28.75%, UA = 90.04%, EU = 27.04% and at CP-02 it is MA = 83.31%, PA = 32%, UA = 94% and EU = 30%. The production of the crusher unit after improving the working time constraints is able to produce 328,021.15 tons/month.